Further evaluation of a multiplex PCR for differentiation of Salmonella paratyphi A from other salmonellae - Teh, Cindy Shuan Ju; Chua, Kek Heng; Puthucheary, Savithri Devi; Thong, Kwai Lin (Institute of Infectious Diseases, 2008)
Salmonella enterica serovar Paratyphi A is a causative agent of paratyphoid fever. The clinical syndrome caused by paratyphoid fever overlaps with other febrile illnesses and cannot be distinguished from typhoid fever. Conventional methods used for diagnosis are time consuming, costly, and labor-intensive. We evaluated the specificity, sensitivity, and application of a multiplex polymerase chain reaction (PCR) previously developed by the method (Ou, H.Y., Teh, C.S.J., Thong, K.L., et al., J. Mol. Diagn., 9, 624-630, 2007) using 6 S. Paratyphi A, 22 S. Typhi, and 85 other Salmonella serovars as well as 36 non-Salmonella strains. The detection limit of the multiplex PCR was 4 x 10(4) cfu ml(-1). In a blind test of the other 50 strains, this multiplex PCR correctly identified the only S. Paratyphi A in the panel of strains. The sensitivity of this PCR using spiked blood and stool samples was 1 x 10(5) cfu ml(-1) and 2 x 10(5) cfu ml(-1), respectively, but increased to 1 x 10(4) cfu ml(-1) and 2 x 10(3) cfu ml(-1) after 5-h enrichment. We believe that this multiplex PCR is a promising technique for the specific and sensitive detection of S. Paratyphi A in clinical, environmental, and food samples.